2017
DOI: 10.1002/slct.201700499
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Anti‐Cancer Activities of Benzyl Analogues of Garlic‐Derived Diallyl Disulfide (DADS) and the Corresponding Diselenides

Abstract: The anti‐cancer activity of garlic mainly arises due to the presence of various organosulfur compounds including diallyl sulfide (DAS), diallyl disulfide (DADS) and diallyl trisulfide (DATS). Herewith, we report a number of 4‐substituted benzyl analogs of DADS and their selenium counterparts for a detailed structure‐activity relationship towards their anti‐proliferative activities in human breast cancer cell lines. Disulfide having 4‐cyano group exhibited highest activity among all disulfides. In contrast, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Moreover, Bhattacherjee et al ( 28 ) recently stated that bis(4-cyanobenzyl)disulfide exhibited the highest antiproliferative activity, among all the 4-substituted benzyl analogues of diallyl disulfide (DADS) studied, in assays using MCF-7 human breast cancer cell lines. These authors found that the half maximal inhibitory concentration (IC 50 ) values (μ M ) for bis(4-cyanobenzyl)disulfide, DADS, and DBDS were 3.66, 16.76, and 43.60, respectively; whereas toward the normal kidney epithelial cell line (NKE) the respective values were 65.71, 45.43, and 70.11.…”
Section: Dibenzyl Disulfide and Dibenzyl Polysulfidesmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, Bhattacherjee et al ( 28 ) recently stated that bis(4-cyanobenzyl)disulfide exhibited the highest antiproliferative activity, among all the 4-substituted benzyl analogues of diallyl disulfide (DADS) studied, in assays using MCF-7 human breast cancer cell lines. These authors found that the half maximal inhibitory concentration (IC 50 ) values (μ M ) for bis(4-cyanobenzyl)disulfide, DADS, and DBDS were 3.66, 16.76, and 43.60, respectively; whereas toward the normal kidney epithelial cell line (NKE) the respective values were 65.71, 45.43, and 70.11.…”
Section: Dibenzyl Disulfide and Dibenzyl Polysulfidesmentioning
confidence: 99%
“…In some instances, it is possible to quantitatively correlate biological outcomes with only one parameter: If the RDS is a chemical reaction, this parameter is often pKa, a Hammett electronic substituent constant, or a Taft steric substituent constant ( 92 ). In the following paragraphs, we will describe a particularly interesting and pertinent linear correlation between the cytotoxicities (Log IC 50 ) of a series of symmetric para-substituted DBDSs and Hammett's sigma substituent constants; the existence of this correlation was overlooked by the authors of the paper from which the data were taken ( 28 ).…”
Section: Dibenzyl Disulfide and Dibenzyl Polysulfidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, other synthetic sulfide derivatives appear to be anti-proliferative in cancer cells, suggesting some commonality in their anti-proliferative effects. This property appears to correspond with the induction of ROS production in cancer cells [108,109] and the S -thiolation of intracellular proteins [110]. Other pronounced biological effects of synthetic sulfide derivatives include neuroprotection by bis [2-(3,4-dimethoxy phenyl) ethenyl] dithioperoxy anhydride and bis [2-(3-methoxy,4-hydroxy phenyl) ethenyl] dithioperoxy anhydride derivatives (Figure 7C,D) [111,112], and cardioprotective properties [113].…”
Section: New Sulfur Compounds Inspired By Allium Metabolitesmentioning
confidence: 99%